Recent trends in seroprevalence of syphilis in different patient groups attending a regional centre for sexually transmitted infections in central India - Datkar, Radha D.; Agrawal, Gopal N.; Gosavi, Sonali S.; Deogade, Kalindi S.; Sharma, Manisha K.; Agarwal, Vandana A. (International Journal of Research in Medical Sciences, 2023)
Background: Easy access to Suraksha clinics for sexually transmitted infections calls for a review of seroprevalence of syphilis. Methods: Serum samples from attendees of sexually transmitted infections (STI)/ reproductive tract infections (RTI) clinic/antenatal clinic, and samples of high-risk group (HRG: female sex workers and men having sex with men) brought by non-government organizations from 2017-22 were screened for syphilis by Venereal Disease Research Laboratory (VDRL) and Treponema pallidum hemagglutination (TPHA) tests. Samples positive by both tests were considered seropositive for syphilis. Statistical methods used for analysis were chi square test for linear trends and Kruskal Wallis test. Results: In STI clinic percentage positivity for syphilis has shown a statistically significant decline from 2017-22. In RTI clinic the decline was significant from 2017-19 but not significant in the years 2019-22. In antenatal clinic and in HRGs the change in seroprevalence was not significant from 2017-22 and 2017-20 respectively. However, the HRGs showed a significantly increasing trend in syphilis seropositivity from 2020-22. Conclusions: There is a significantly declining trend in the seroprevalence of syphilis in patients attending the STI/RTI clinic from 2017-22 and in HRGs from 2017-20. However, a significant increase in trend in HRG from 2020-22 may have been due to behavioural changes during the lockdown for covid 19 pandemic. A significant decline in syphilis in patients attending the STI and RTI clinic and in HRGs attending the regional centre indicates the effectiveness of consistent detection, treatment and counselling efforts of the national control program on STI in the region.